Differential effects of alliance and techniques on Panic-Specific Reflective Function and misinterpretation of bodily sensations in two treatments for panic. (2nd January 2020) - Solomonov, Nili; Falkenström, Fredrik; Gorman, Bernard S.; McCarthy, Kevin S.; Milrod, Barbara; Rudden, Marie G.; Chambless, Dianne L.; Barber, Jacques P.
ABSTRACT : Objective: To examine whether working alliance quality and use of techniques predict improvement in Panic-Specific Reflection Function (PSRF), and misinterpretation of bodily sensations in treatments for panic disorder. Method: A sample of 161 patients received either CBT or PFPP (Panic-focused Psychodynamic therapy) within a larger RCT. Data were collected on patient-reported working alliance, misinterpretations, PSRF, observer-coded use of techniques, and interviewer-rated panic severity. Random-Intercept Cross-Lagged Panel Models assessed bi-directional associations, disentangling within- and between-patient effects, and accounting for prior change. Results: Higher alliance predicted subsequent within-patient improvement in PSRF in PFPP, but worsening in CBT. In both treatments, focus on interpersonal relationships predicted PRSF improvement (with stronger effects in CBT), while focus on thoughts and behaviors predicted worsening in PSRF. In CBT only, early focus on affect and moment-to-moment experience predicted reduced misinterpretation, while high focus on thoughts and cognitions predicted subsequent increase in misinterpretation. Conclusion: The quality of the alliance has differential effects on PSRF in distinct treatments. Interpersonal, rather than cognitive or behavioral focus, even when delivered differently within distinct treatments with high adherence, could facilitate improvement in PSRF. Additionally, early focus on affect and moment-to-moment experiences in CBT could reduce misinterpretations.